2020
DOI: 10.1177/0731121420964785
|View full text |Cite
|
Sign up to set email alerts
|

Information-seeking in the Wake of Tragedy: An Examination of Public Response to Mass Shootings Using Google Search Data

Abstract: Mass shootings are a highly visible form of violence in the United States, although public response to these events varies considerably. Drawing on social problems and collective threat perception literature, we use search data for all Google-using Americans following mass shootings since 2004 to examine how event attributes such as the number of victims, venue, and type of weapon(s) predict public information-seeking related to gun control and gun rights. The results demonstrate that the number of victims, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The last two decades have shown the capacity for technological development and the human ability to incorporate it into daily routines [9][10][11]31,32,35]. In the case of the Internet, its birth and evolution have meant a before and after in humanity [12,13,33,34], and has altered the way people communicate and collaborate [1,18]. Having and using a smartphone [21], even becoming addicted [51], or spending time on social networks [2] are new patterns of behavior in a society where digital skills are becoming essential [26,27,29,36,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two decades have shown the capacity for technological development and the human ability to incorporate it into daily routines [9][10][11]31,32,35]. In the case of the Internet, its birth and evolution have meant a before and after in humanity [12,13,33,34], and has altered the way people communicate and collaborate [1,18]. Having and using a smartphone [21], even becoming addicted [51], or spending time on social networks [2] are new patterns of behavior in a society where digital skills are becoming essential [26,27,29,36,38].…”
Section: Discussionmentioning
confidence: 99%
“…This is an interest that responds to a historical moment in which social networks offer the right possibilities to cover everything from the individual to the social [31], including work [32]. Some of the main characteristics that may justify this phenomenon are: being a quick and easy alternative to access a wide range of information [33,34], offering almost instantaneous interaction and communication [35], opening up business possibilities in global environments and not just local ones [36], and even serving as a parallel strategy to find out preferences and interests in particular issues [37]. These applications accompany the new digital habits, especially among the young, whose interest in the more classic media is declining and who are developing new digital skills in areas such as content consumption [38].…”
Section: Introductionmentioning
confidence: 99%
“…While actual exposure to a death cannot be tested directly with these data, it is possible to determine the visibility of a death more generally using Google Trends. 5 Several papers have used Google Trends data as a measure of public attention to particular phenomena (Lee, Kim, and Scheufele 2016; Semenza and Bernau 2020). This service “analyzes a percentage of Google web searches to determine how many searches were done over a certain period of time.” 6 For any search term entered, Google Trends returns a number between 0 to 100 that indicates the popularity of that search term relative to others within a certain location and time period.…”
Section: Datamentioning
confidence: 99%
“…Several recent studies reported data-driven models and frameworks to study mass violence, including [ 16 , 17 ]. Public response data can also be employed to model the violence at the mass level [ 18 ]. However, comparatively, it is challenging to consider social media and news media as a structured sources of information that can be credible and robust for such studies.…”
Section: Introductionmentioning
confidence: 99%